PSYCHOLOGICAL MODELS FOR ATTITUDINAL AND PERSUASION CHANGES IN CONSUMER BEHAVIOUR - L. Spasova; Zh. Gundasheva (Trakia Journal of Sciences)
The present study explores psychological models for changing consumers’ attitudes under the influence of advertisements in young people of 18 to 25 years of age. The aim of the study is to establish the influence of the advertisements of mobile phone operators on the attitudes, consumer thinking and behaviour of youth with respect to mobile products and services. The following tasks were set:  To study the advertisements of mobile phone operators in Bulgaria  To set a theoretical frame on consumers’ attitudes  To determine the models of attitudinal change and persuasion  To perform correlational analyses of statistically significant factors The methods used to achieve these tasks are the following: conducting two subsequent surveys on the same respondents regarding their behavior before, during and after exposure to advertisement; holding individual interviews with random young respondents.